ENGAGING STIGMA: AN EMBODIED THEOLOGICAL RESPONSE TO HIV AND AIDS - Ackermann, Denise (Scriptura, 2005)
This paper explores the nature of stigma in relation to HIV/Aids by way of fifteen interrelated observations. It serves as an example of "embodied theology". It also offers reflections on what could constitute an appropriate response to stigma on the part of communities of faith in order to clarify and strengthen their roles in combating the Aids pandemic. "Thembi" grew thin, lost her appetite and then became too weak to get out of bed. "I asked my mother to come from the Transkei to nurse me because my boyfriend had gone back to Maputo. I cannot tell my mother that I have the ‘new sickness’. She thought I had been ‘toored’ (bewitched) and sent for the sangoma (healer) to rub me with herbs to chase the demons out. Nothing helps. Now I am afraid that Sisi is also sick. What will happen to her? I can’t tell my church. They will judge me." ("Thembi" died two weeks later in a backroom of one of Johannesburg’s suburbs at the age of 29. Her boyfriend arrived in time to bury her. Her daughter Sisi now lives with her grandmother and she is showing signs of being infected with HIV).2 "Lunga was so excited that morning. He was going to pre-school, face shining, clutching his sandwiches. I had told the school that he was HIV-positive. They accepted him. Things went well and Lunga thrived. Then someone broke confidentiality and told a parent that he was HIV positive. News spreads quickly. I noticed hostility when I took him to school, and then he came home crying. Parents in his class had forbidden their children to play with him. We had to remove him. It has been very hard. We know what stigma feels like and Lunga is lonely." (Louisa, foster mother of Lunga, aged 4). "My family is very conservative. They are good people; they read their Bibles, they go to church, they pay their taxes but they never talk about sex. They simply don’t understand about life today. I can’t tell them the truth. They won’t understand, they won’t know what to do with me. I think they will judge me and I can’t bear any more judgment. I am not a bad person. I just made a mistake, I was stupid and I am paying for it. The worst is not the virus but the judgment." (Annatjie, a student aged 24, who recently discovered her status.)